Potential roads for reaching the summit: an overview on target therapies for high-grade gliomas - Giotta Lucifero , Alice; Luzzi, Sabino; Brambilla, Ilaria; Schena, Lucia; Mosconi, Mario; Foiadelli, Thomas; Savasta, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
The tailored targeting of specific oncogenes represents a new frontier in the treatment of high-grade glioma in the pursuit of innovative and personalized approaches. The present study consists in a wide-ranging overview of the target therapies and related translational challenges in neuro-oncology. Methods: A review of the literature on PubMed/MEDLINE on recent advances concerning the target therapies for treatment of central nervous system malignancies was carried out. In the Medical Subject Headings, the terms “Target Therapy”, “Target drug” and “Tailored Therapy” were combined with the terms “High-grade gliomas”, “Malignant brain tumor” and “Glioblastoma”. Articles published in the last five years were further sorted, based on the best match and relevance. The ClinicalTrials.gov website was used as a source of the main trials, where the search terms were “Central Nervous System Tumor”, “Malignant Brain Tumor”, “Brain Cancer”, “Brain Neoplasms” and “High-grade gliomas”. Results: A total of 137 relevant articles and 79 trials were selected. Target therapies entailed inhibitors of tyrosine kinases, PI3K/AKT/mTOR pathway, farnesyl transferase enzymes, p53 and pRB proteins, isocitrate dehydrogenases, histone deacetylases, integrins and proteasome complexes. The clinical trials mostly involved combined approaches. They were phase I, II, I/II and III in 33%, 42%, 16%, and 9% of the cases, respectively. Conclusion: Tyrosine kinase and angiogenesis inhibitors, in combination with standard of care, have shown most evidence of the effectiveness in glioblastoma. Resistance remains an issue. A deeper understanding of the molecular pathways involved in gliomagenesis is the key aspect on which the translational research is focusing, in order to optimize the target therapies of newly diagnosed and recurrent brain gliomas.